THE RELATION OF ATHEROGENIC OXIDATIVE-ANTIOXIDANT SHIFTS IN LOW DENSITY LIPOPROTEIDES WITH ADVERSE LONG-TERM PROGNOSIS IN MALES - Yu. I. Ragino; M. I. Voevoda; S. K. Malyutina; V. V. Gafarov; S. V. Shishkin; S. N. Bogatyrev; L. V. Scherbakova; Ya. V. Polonskaya (Российский кардиологический журнал, 2016)
Aim. To study the baseline parameters of potentially atherogenic oxidativeantioxidant changes of low-density lipoproteides (LDL) with adverse 7-year longterm outcomes.Material and methods. In male population (n=1024, aged 47-73 year-old) by biochemistry we assessed the values of baseline and catalyzation stimulated oxidation of peroxidated lipids products (LOP) in LDL, concentration of antioxidants in LDL (alpha-tocopherol, beta-carotene, retinol, xantines), concentration of antibodies to oxidized LDL (oxLDL). Then, during 7 years with the use of Registers we assessed endpoints: myocardial infarction, stroke, total and cardiovascular mortality.Results. The significant associations revealed, of the baseline LDL products content (p=0,019, Hazard Ratio, HR=1,39) and resistance of LDL to oxidation at early stage (p=0,048, HR=1,18) with the stroke cases. Also, the significant relations found of beta-carotene in LDL (p=0,034, HR=0,98) and antibodies concentration against oxLDL (p=0,041, HR=0,99) with cardiovascular mortality cases in 7 year follow-up.Conclusion. The data represents significant pathogenetic role of atherogenic oxidation-antioxidant changes of LDL in development of cardiovascular diseases and complications.